PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KREATIVITAS BELAJAR SISWA KELAS IX DI UPT SPF SMP NEGERI 21 MAKASSAR - Nur Maulidyah; Nurindah; Nasir (STKIP Subang, 2024)
The low level of student creativity in the learning process is often caused by conventional teaching methods which are less effective in encouraging students to think creatively and solve problems independently. This problem is an important concern in the world of education. This research aims to identify the influence of using the Project Based Learning model on the learning creativity of class IX students at UPT SPF SMP Negeri 21 Makassar. The research sample consisted of 136 class IX students at the school. The results of research and data analysis show that the use of Project Based Learning media significantly increases students' learning creativity, as demonstrated through descriptive statistical analysis. The results of the questionnaire showed that the category of application of learning models reached 96.46% in the very high category, while student learning creativity reached 97.10% in the very high category. Apart from that, based on inferential statistical analysis using the Pearson correlation test, a correlation coefficient of 0.558 was obtained with a significance value of 0.000, which means it is significant at the 0.05 level. Thus, the results of this research conclude that there is a significant increase in student learning creativity related to the use of the Project Based Learning model in class IX UPT SPF SMP Negeri 21 Makassar.Keywords: Multimedia Interactive Media, Learning Motivation, Science.